Apple seeds in an excavated Roman amphora remained intact for 2000 years despite exposure to a broadly-degrading microbial community. (June 2019) - Milanesi, Claudio; Faleri, Claudia; Cresti, Mauro; Andreolli, Marco; Lampis, Silvia; Vallini, Giovanni; Sfriso, Andrea; Gallo, Michele; Baldi, Franco
Abstract: During the first century BCE, a devastating fire destroyed a Roman villa on Elba Island (Tuscany, Italy) but 500 non-carbonized apple seeds were recovered from within four amphorae buried 1.5 m underground level. Most of the seeds had deteriorated, but 63 showed intact integument and embryo tissues suggesting they were unable to germinate. The seeds were coated in a clay-like organic layer baked into place during the fire covering a caramelized amorphous matrix generated by the transformation of sugars. The seeds inside this shield were protected from physicochemical and biological deterioration, even though fungal hyphae and bacteria were identified inside the embryos by DAPI staining. Some microbial strains were retrieved from the seed tissue, including the ascomycete Aspergillus awamori and bacteria of the genera Bacillus and Variovorax . In contrast, the protective layer around the seed yielded Enterobacteriaceae such as the genera Citrobacter and Salmonella, along with Pseudomonas and Streptomyces, and the fungi Thermothelomyces thermophila and Humicola fuscoatra, which are renowned for their resistance to heat. PCR-DGGE analysis showed no correspondence between 16S rRNA gene sequences isolated from the protective layer covering the seed and from within the seed tissues. Despite the presence of a diverse microbial population, the protective coat on the ancient seeds prevented the deterioration of about 20% of seeds, allowing a comparison to the present-day seeds of Malus sylvestris, the botanical species which the archaeological finds represents. Highlights: One Roman amphora 2000 years old containing 63 intact apple seeds, was excavated. Apple seeds contained first-century microbial community. Spore-forming microorganisms were revitalized from archaeological seeds. Recovery of DNA sequences of microbial communities Identification of cultivable strains Aspergillus awamori, Bacillus sp. and Variovorax sp.